Therapeutic Potential of Targeting PI3K/AKT Pathway in Treatment of Colorectal Cancer: Rational and Progress. Issue 3 (15th May 2017) - Bahrami, Afsane; Khazaei, Majid; Hasanzadeh, Malihe; ShahidSales, Soodabeh; Joudi Mashhad, Mona; Farazestanian, Marjaneh; Sadeghnia, Hamid Reza; Rezayi, Majid; Maftouh, Mina; Hassanian, Seyed Mahdi; Avan, Amir
ABSTRACT: PI3K/AKT/mTOR signaling pathway is one of the key dysregulated pathways in different tumor types, including colorectal cancer (CRC). Activation of this pathway is shown to be related with cellular transformation, tumor progression, cell survival, and drug resistance. There is growing body of data evaluating the value of PI3K/AKT/mTOR inhibitors in CRC (e.g., BEZ235, NVP‐BEZ235, OSI‐027, everolimus, MK‐2206, KRX‐0401, BYL719, and BKM120). This report summarizes the current knowledge about PI3K/AKT pathway and its cross talk with ERK/MAPK and mTOR pathways with particular emphasis on the value of targeting this pathway as a potential therapeutic target in treatment of colorectal cancer. J. Cell. Biochem. 119: 2460–2469, 2018. © 2017 Wiley Periodicals, Inc. Abstract : PI3K/AKT/mTOR signaling pathway is one of the key dysregulated pathways in different tumor types, including colorectal cancer (CRC). Activation of this pathway is shown to be related with cellular transformation, tumor progression, cell survival, and drug resistance. There is growing body of data evaluating the value of PI3K/AKT/mTOR inhibitors (e.g., BEZ235, NVP‐BEZ235, OSI‐027, everolimus, MK‐2206, KRX‐0401, BYL719, and BKM120). This report summarizes the current knowledge about PI3K/AKT/mTOR pathway and its cross talk with ERK/MAPK and mTOR pathways with particular emphasis on the value of targeting this pathway as a potential therapeutic target in treatment of colorectal cancer.